Egg-guarding behaviour in the Antarctic bathydraconid dragonfish Parachaenichthys charcoti - Barrera Oro, Esteban; Lagger, Cristian Fabian (Polar Biology)
This paper provides the first photographic evidence of nest-guarding posture in the Antarctic bathydraconid Parachaenichthys charcoti in its natural habitat. Because bathydraconids are not monophyletic and P. charcoti is included in a different clade than Gymnodraco acuticeps, there is now documentation of nest guarding in all major clades of Antarctic notothenioids except for the Artedidraconidae. Fil: Barrera Oro, Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Lagger, Cristian Fabian. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina